Review Farmakoterapi Diabetes Melitus - irma novrianti (JURNAL FARMASI DAN MAKANAN, 2022)
Diabetes Mellitus (DM) is a non-communicable disease in which blood glucose levels in the body is high as a result of reduced production of insulin produced in the liver. The prevalence of DM continues to increase every year and if this disease is not treated, it can lead to further complications, such as diabetic neuropathy, diabetic retinopathy, and diabetic nephropathy. This review article aims to provide a review of diabetes mellitus so that the early diagnosis of this disease can lead to reduction in the risk of complications. This article uses original articles such as Literature Review, and National and International Research Reports published from 2012 to 2021 which were obtained from Google search engine, Google Scholar, and Pubmed. DM is a disease caused because of the incapability of pancreatic beta cells to produce insulin hormones. Insulin is a hormone that has a function in facilitating cellular glucose uptake. DM is divided into type 1 DM and type 2 DM. Type 1 diabetes occurs due to destruction of pancreatic cells, and type 2 diabetes occurs due to resistance to insulin receptors. The risk factors for DM are genetic, age, gender, lifestyle and obesity. DM therapy currently used, such as oral antidiabetic drugs, and insulin and also lifestyle changes which consist of increasing physical activity such as exercise